BNIP3-dependent mitophagy promotes cytosolic localization of LC3B and metabolic homeostasis in the liver. Issue 11 (2nd November 2021) - Springer, Maya Z.; Poole, Logan P.; Drake, Lauren E.; Bock-Hughes, Althea; Boland, Michelle L; Smith, Alexandra G.; Hart, John; Chourasia, Aparajita H.; Liu, Ivan; Bozek, Grazyna; Macleod, Kay F
ABSTRACT: Mitophagy formed the basis of the original description of autophagy by Christian de Duve when he demonstrated that GCG (glucagon) induced macroautophagic/autophagic turnover of mitochondria in the liver. However, the molecular basis of liver-specific activation of mitophagy by GCG, or its significance for metabolic stress responses in the liver is not understood. Here we show that BNIP3 is required for GCG-induced mitophagy in the liver through interaction with processed LC3B; an interaction that is also necessary to localize LC3B out of the nucleus to cytosolic mitophagosomes in response to nutrient deprivation. Loss of BNIP3-dependent mitophagy caused excess mitochondria to accumulate in the liver, disrupting metabolic zonation within the liver parenchyma, with expansion of zone 1 metabolism at the expense of zone 3 metabolism. These results identify BNIP3 as a regulator of metabolic homeostasis in the liver through its effect on mitophagy and mitochondrial mass distribution. Abbreviations: ASS1, arginosuccinate synthetase; BNIP3, BCL2/adenovirus E1B interacting protein 3; CV, central vein; GCG – glucagon; GLUL, glutamate- ammonia ligase (glutamine synthetase); HCQ, hydroxychloroquine; LIR, LC3-interacting region; MAP1LC3B/LC3B, microtubule-associated protein 1 light chain 3 beta; mtDNA:nucDNA, ratio of mitochondrial DNA to nuclear DNA; PV, periportal vein; TOMM20, translocase of outer mitochondrial membrane protein 20.